Snakeskin Gourami (Trichogaster pectoralis) Stick High in Protein and Calcium as of Fish Product Diversification - Dewi Kartika Sari; Hafni Rahmawati; Susilawati Susilawati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Snakeskin gourami (Trichogaster pectoralis) is a freshwater fish often consumed by the people of South Kalimantan. The meat and the bones of this fish can be processed into protein and calcium-rich fish sticks. This study was aimed to analyze the sensory and chemical characteristics of snakeskin gourami stick. The meat and bones of the fish were added into sticks ingredients with the proportion of 0; 20; 40 and 60%. The results showed that the addition of fish meat and bones significantly affected the sensory characteristics particularly on the aroma and the taste of fish sticks, as well as the chemical quality including protein, fat, carbohydrate, water, ash, and calcium content. The sticks made with 60% of the fish meat and bones were more preferred and gave better chemical characteristics than those made with the other proportions.